A systematic review of compliance with indoor tanning legislation - Jessica Reimann; Jennifer E. McWhirter; Andrew Papadopoulos; Cate Dewey (BMC, 2018)
Abstract Background Many jurisdictions have enacted indoor tanning legislation in response to the health risks of artificial ultraviolet (UV) radiation exposure. Key components of these legislations include banning minors' access, requiring parental consent or accompaniment, providing protective eyewear, posting health warning signs, and communicating important health risk information. However, legislation must be complied with to be impactful. Evidence around compliance with indoor tanning legislations has not been synthesized and is an important step toward determining changes in practice due to legislation. Methods A systematic review was conducted to obtain peer-reviewed literature about compliance with indoor tanning legislation worldwide. Six databases were searched, resulting in 12,398 citations. Sixteen studies met the inclusion criteria (peer-reviewed scientific studies, published in English, focused primarily on compliance with indoor tanning legislations, and focused on commercial indoor tanning in indoor tanning facilities). Results Compliance with most aspects of indoor tanning legislation varied widely. There was good compliance for provision of protective eyewear (84 to 100%; mean = 92%; SD = 8). Compliance with age restrictions ranged from 0 to 100% (mean = 65%; SD = 25), while compliance with posting warning labels in the required locations within a tanning facility ranged from 8 to 72% (mean = 44%; SD = 27). Variation in compliance may be due to true differences, study methodology, or temporal trends. Conclusions Variability in compliance with indoor tanning legislation, as found in this systematic review, indicates the legislations may not be having their intended protective effects on the public's health. The reasons for such low and varied compliance with certain aspects of legislation, and high compliance with other aspects of legislation, deserve further attention in future research to inform best practices around ensuring high and consistent compliance with indoor tanning legislations worldwide.